MACC1 expression is an indicator of recurrence in early-stage glottic cancer. (28th December 2019) - Makino, Takuma; Orita, Yorihisa; Gion, Yuka; Tachibana, Tomoyasu; Takao, Soshi; Marunaka, Hidenori; Miki, Kentaro; Akisada, Naoki; Akagi, Yusuke; Yoshino, Tadashi; Nishizaki, Kazunori; Sato, Yasuharu
Abstract: Background: Metastasis-associated in colon cancer 1 (MACC1) has been reported to be an independent indicator of poor prognoses in some kinds of cancer due to disease metastasis or recurrence. We investigated the correlation between MACC1 expression and the prognosis of glottic cancer. Methods: Paraffin-embedded, early-stage (I or II) glottic cancer specimens ( n = 52) were immunohistochemically analyzed to explore MACC1 expression. The clinical records associated with each case were also examined. Recurrence-free survival (RFS) was estimated using the Kaplan–Meier method, and between-group RFS differences were assessed using the log-rank test. The multivariate analyses were evaluated using the Cox's proportional-hazard model. Results: Patients were treated with only radiotherapy (RT) ( n = 37, including 18 with T1 disease and 19 with T2 disease), or with chemoradiotherapy (CRT) ( n = 15, including 1 with T1 disease and 14 with T2 disease). Eleven patients demonstrated local recurrence and two patients experienced cervical lymph node recurrence. Tumor specimens were MACC1-positive in 9 of the 13 (69.2%) patients with local or neck recurrence, and 7 of the 11 (63.6%) patients with local recurrence. The RFS rate of patients who were treated with only RT was significantly lower than that of patients who were treated with CRT ( P = 0.0243). The RFS rate was significantly lower in cases with MACC1 expression than in those without MACC1 expression ( P = 0.0003). Multivariate analysis revealed that MACC1 expression was an independent risk factor of local recurrence ( P = 0.0016). Conclusion: MACC1 is an independent indicator of recurrence related to RFS in early-stage glottic cancer. Abstract : Metastasis-associated in colon cancer 1 (MACC1) is an independent indicator of recurrence in early-stage glottic cancer.